Student Satisfaction with Hostel Facilities: A Case Study of Njala University, Njala Campus, Sierra Leone - Williams, Samuel Maxwell Tom; Osborne, Augustus; Bangura, Camilla; Johnny, Jonathan; Bakarr, Ibrahim A.; Koroma, Alusine Hassan; Saidu, Janet Boynah; Musa, Jonathan Aruna; Fefegula, George Mayeh (European Scientific Journal, ESJ, 2022)
Aim and Scope: The importance of students’ social environments in their day-to-day lives cannot be overstated. The extent to which students are happy in their hostel depends on its facilities’ availability, adequacy, and functionality. A case study of Njala University, Njala campus, was used to determine the amenities provided and the level of satisfaction the students derived from those amenities. Methods: A cross-sectional research design was used to conduct the research through a close-ended questionnaire. The study’s sample size was 482 students. SPSS version 26.0 was used for the data analysis. Result: Most (82.0%) of the respondents were within the age group 20-29 years, and more than two-thirds (70.7%) were living in overcrowded rooms with double the number than the room was designed for.; this is attributed to the common phenomenon of students who get a place sub-letting to their less fortunate colleagues on a cost-sharing basis. Overcrowding has implications of increasing pressure on the available facilities. Students were reasonably satisfied with hostel facilities such as recreational grounds, security status, Library/ICT, waste management, and electricity, but very dissatisfied with the drainage system, state of mattresses, toilet facilities, water supply, kitchen, room size, laundry, and lack of firefighting devices. Conclusion : Students are dissatisfied with current facilities as enrollment continues to rise faster than Government intervention the paper suggests that a public-private partnership be established to fund the construction of other hostels with updated designs and amenities.